Relationship between internucleotide linkage geometry and the stability of RNA. - Soukup, G A (1999)
The inherent chemical instability of RNA under physiological conditions is primarily due to the spontaneous cleavage of phosphodiester linkages via intramolecular transesterification reactions. Although the protonation state of the nucleophilic 2'-hydroxyl group is a critical determinant of the rate of RNA cleavage, the precise geometry of the chemical groups that comprise each internucleotide linkage also has a significant impact on cleavage activity. Specifically, transesterification is expected to be proportional to the relative in-line character of the linkage. We have examined the rates of spontaneous cleavage of various RNAs for which the secondary and tertiary structures have previously been modeled using either NMR or X-ray crystallographic data. Rate constants determined for the spontaneous cleavage of different RNA linkages vary by almost 10,000-fold, most likely reflecting the contribution that secondary and tertiary structures make towards the overall chemical stability of RNA. Moreover, a correlation is observed between RNA cleavage rate and the relative in-line fitness of each internucleotide linkage. One linkage located within an ATP-binding RNA aptamer is predicted to adopt most closely the ideal conformation for in-line attack. This linkage has a rate constant for transesterification that is approximately 12-fold greater than is observed for an unconstrained linkage and was found to be the most labile among a total of 136 different sites examined. The implications of this relationship for the chemical stability of RNA and for the mechanisms of nucleases and ribozymes are discussed.